You are on page 1of 7

Mathematical Methods Coursework

Arbias Junior Gauss Hashani


1 Question 1
We have a circus of radius one hence r = 1 meaning the polar form of z which is z = re
i
= e
i
as r = 1. To
map this circle of radius one into another circle of radius one, the modulus of the transformation must be one
itself. Hence
|T(z)| = 1

az + b
cz + d

= 1 |az + b| = |cz + d|
_
(az + b)(az + b)
_
1
2
=
_
(cz + d)(cz + d)
_
1
2
(az + b)(az + b) = (cz + d)(cz + d) (1)
Expanding equation (1) gives us
aazz + ba + abz + bb = cczz + cdz + cdz + dd (2)
We know that |z| = 1 means zz = 1 and that |a|
2
= aa and similarly for b, c, d we have equation (2) to be
|a|
2
+|b|
2
+ ab + abz = |c|
2
+|d|
2
+ cdz + dcz (3)
Equating coecients of equation (3) gives us
|a|
2
+|b|
2
= |c|
2
+|d|
2
ab = cd
ba = dc
We have three equations with four unknowns. This cannot be solved so we take d = 1 to just have three
unknowns and a solvable form. Then we have
|a|
2
+|b|
2
= |c|
2
+ 1 (4)
ab = c (5)
ba = c (6)
Multiplying expression (5) with (6) gives us |a|
2
, |b|
2
, |c|
2
hence
|a|
2
+|b|
2
= |c|
2
+ 1 (7)
|a|
2
|b|
2
= |c|
2
(8)
Expression (7) minus expression (8) gives us
|a|
2
_
1 |b|
2
_
+|b|
2
= 1 |a|
2
=
1 |b|
2
1 |b|
2
= 1 |a|
2
= 1
This last expression just says that a lies on the unit circle hence a = e
i
(and using that a = 0).
1
Then we just have b = e
i
c. Our transformation T(z) becomes
T(z) =
e
i
z e
i
c
cz 1
= e
i
z c
cz 1
This means that a() = e
i
, b(, ) = e
i
, c() = , d = 1 and we have the desired transformation
T(z) = e
i
z
z 1
How can we have T(z) to leave the unit circle |z| = 1 invariant? We just set |T(z)| = |z|. This expression
should equal 1 as |z| = 1.
If so T(z) is indeed invariant at mapping a unit circle to the unit circle.We are assuming that |z| = 1 not
|T(z)| = 1, this latter expression creates the invariance. We also know that the modulus of a product of two
numbers is the product of the modulus of the individual numbers. Hence
|T(z)| =

e
i
z
z 1

= |z|
..
=1
|z | = |z 1|
(z )(z ) = (z 1)(z 1) zz z z + = zz z z + 1
|z|
2
+||
2
= ||
2
||z|
2
+ 1 (9)
Using that |z| = 1 equation (9) reduces to
1 +||
2
= ||
2
1 = 1 T(z) = 1
Which is what we desired. It shows the modulus of the transformation is equal to 1 hence showing invariance.
Without this step, we cannot proceed.
We want to maps the line passing through the points z
1
= 0 and z
2
=

3+i
2
to the line passing through the
points w
1
= 2(

3 + i) and w
2
=
4

3+11i
13
.
As is complex let = re
i
for some radius r with r > 0 and angle . We have T(z
1
) = w
1
to be
T(z
1
) = w
1
re
i(+)
= 4e
i

6
r = 4 , + =

6
(10)
We have T(z
2
) = w
2
to be (and using equation (10))
T(z
2
) = w
2
e
i(

6
)
e
i

6
4e
i
4e
i(

6
)
1
=
4

3 + 11i
13
(11)
We could simplify this down and solve it, but for mathematical brevity (and noting that this coursework
and mathematics in general is not about solving tedious equations) we see that if we take =

6
and hence
=

3
we have equation (11) to be satised. Again, we could be tedious and expand in terms of cosines and
sines to get a solution but this is not such an important step. What is important is that we have found and
.
Hence we have =

6
, r = 4, = 4e
i

6
and
+ =

6


6
=

6
=

3
And our transformation is
T(z) = e
i

3
z 4e
i

6
4e
i

6
1
2
2 Question 2
We want to show that for every > 0 there exists a > 0 such that |(2 + i)z (1 + 3i)| < for all values of
z for which |z (1 + i)| < . We could just pick the required right away but instead let us show how we get
there.
|(2 + i)z (1 + 3i)| <
1
|2 + i|
|(2 + i)z (1 + 3i)| <

|2 + i|

z
1 + 3i
2 + i

<

|2 + i|
|z (1 + i)| <

|2 + i|
The last expression is in the form which implies the limit. Take = |2 + i| =

5. Then we have
|z (1 + i)| < |z (1 + i)| <

|2 + i|
|(2 + i)z (1 + 3i)| <
Proven.
3 Question 3
3.1 f(x, y) = e
x
2
y
2
cos(2xy)
The functions e
x
2
y
2
and cos(2xy) are dierentiable everywhere hence analytic. Their derivatives exist and the
product of these two function f(x, y) = e
x
2
y
2
cos(2xy) is also analytic, so we use the product rule to nd the
well dened partial derivatives f
x
, f
y
, f
xx
and f
yy
.
f
x
= e
x
2
y
2
(2xcos(2xy) 2y sin(2xy))
f
xx
= e
x
2
y
2 _
cos(2xy)(4y
2
+ 2 + 4x
2
) 8xy sin(2xy)
_
f
y
= e
x
2
y
2
(2xsin(2xy) + 2y cos(2xy))
f
yy
= e
x
2
y
2 _
cos(2xy)(4y
2
+ 2 + 4x
2
) 8xy sin(2xy)
_
We see that f
xx
+ f
yy
= 0, so f is harmonic.
To construct the conjugate harmonic function, suppose we have some analytic function A(x, y) = f(x, y) +
iz(x, y). We want to nd z(x, y).
The Cauchy-Riemann equations tell us f
x
= z
y
and f
y
= z
x
for the analytic function A(x, y). Hence we
have
f
x
= e
x
2
y
2
(2xcos(2xy) 2y sin(2xy)) = z
y
(12)
f
y
= e
x
2
y
2
(2xsin(2xy) + 2y cos(2xy)) = z
x
(13)
Integrating equation (12) with respect to y and integrating equation (13) with respect to x gives us
_
f
x
dy =
_
z
y
dy = z(x, y) + c
1
We show two dierent ways of solving the required integral. A tedious, standard way (integration by parts)
and another to capture the imagination between integration and dierentiation (error functions).
Method 1: Integration by parts
z(x, y) + c
1
=
_
e
x
2
y
2
(2xcos(2xy) 2y sin(2xy)) dy =
_
e
x
2
y
2
2xcos(2xy) dy
. .
I
1

_
e
x
2
y
2
2y sin(2xy)
. .
I
2
dy
(14)
Performing integration by parts on I
1
gives us I
1
= e
x
2
y
2
sin(2xy) + 2y
_
e
x
2
y
2
sin(2xy) dy.
Inserting this into equation (14) gives us
z(x, y) = e
x
2
y
2
sin(2xy) + 2y
_
e
x
2
y
2
sin(2xy) dy 2y
_
e
x
2
y
2
sin(2xy) dy = e
x
2
y
2
sin(2xy) + (x) (15)
For some function of x and the constant c
1
is absorbed into .
3
Similarly equation (13) is just
z(x, y) + c
2
=
_
e
x
2
y
2
(2xsin(2xy) + 2y cos(2xy)) dx =
_
e
x
2
y
2
2xsin(2xy) dx
. .
I
3
+e
x
2
y
2
2y cos(2xy) dx
. .
I
4
(16)
Integration by parts on I
4
gives us I
4
= e
x
2
y
2
sin(2xy) 2x
_
e
x
2
y
2
sin(2xy) dx. Inserting this back into
equation (16) gives us
z(x, y) =
_
e
x
2
y
2
2xsin(2xy) dx
_
e
x
2
y
2
2xsin(2xy) + e
x
2
y
2
sin(2xy) = e
x
2
y
2
sin 2xy + (y) (17)
For some function of y and the constant c
2
is absorbed into .
Equations (15) and (17) imply that (y) = (x) = 0 and we just have z(x, y) = e
x
2
y
2
sin(2xy) hence
A(x, y) = e
x
2
y
2
cos(2xy) + ie
x
2
y
2
sin(2xy)
Method 2: Fun With Error Functions
Suppose we are not satised with integration by parts and want to have some fun!
As we have an analytic function we can exchange the dierentiation and integration operations to get
_
f
x
dy =

x
_
f(x, y) dy =

x
_
e
x
2
y
2
cos(2xy) dy (18)
Now the magic begins. Expressing f as a pure exponential gives us f(x, y) =
1
2
e
x
2
2xiyy
2
+
1
2
e
x
2
+2xiyy
2
.
Inserting this into equation (18) gives us

x
_
f(x, y) dy =
1
2

x
e
x
2
_
e
2xiyy
2
dy +
1
2

x
e
x
2
_
e
2xiyy
2
dy
Completing the square for both integrals gives us
1
2

x
_
e
(yix)
2
dy +
1
2

x
_
e
(y+ix)
2
dy
These two integrals are just scaled error functions, so we have

x
_
i
4

erf(ix y)
i
4

erf(ix + y)
_
Dierentiating with respect to x gives us
i
2
_
e
(ixy)
2
e
(ix+y)
2
_
which is the same as
z(x, y) = e
x
2
y
2
sin(2xy)
We then just proceed as we have done for the rst method.
3.2 g(x, y) = arctan(
y
x
)
This function is well behaved everywhere except at x = 0. When we dierentiate we have our domain to include
everything but this point.
g(x, y) = arctan(
y
x
) tan(g(x, y)) =
y
x
(19)
Dierentiating both sides of equation (19) with respect to y gives us

y
tan(g(x, y)) =

y
y
x
(20)
Using standard rules of dierentiation we have equation (20) to just be
g
y
sec
2
(g(x, y)) =
1
x

g
y
=
1
xsec
2
(g(x, y))
(21)
4
Using the relationship sec
2
(g(x, y)) = tan
2
(g(x, y)) + 1 means equation (20) is just
g
y
=
1
x
_
tan
2
(g(x, y)) + 1
_ =
1
x
_
y
2
x
2
+ 1
_
Using the quotient rule on this to nd g
yy
we just have
g
yy
=
2xy
(x
2
+ y
2
)
2
The similar case for dierentiating with respect to x holds and we have the partial derivatives to be
g
x
=
y
x
2
+ y
2
g
xx
=
2xy
(x
2
+ y
2
)
2
g
y
=
x
x
2
+ y
2
g
yy
=
2xy
(x
2
+ y
2
)
2
We see that g
xx
+ g
yy
= 0 hence g is harmonic.
To construct the conjugate harmonic function, suppose we have some analytic function B(x, y) = g(x, y) +
ip(x, y). We want to nd p(x, y).
The Cauchy-Riemann equations tell us g
x
= p
y
and g
y
= p
x
for the analytic function B(x, y). Hence we
have
g
x
=
y
x
2
+ y
2
= p
y
(22)
g
y
=
x
x
2
+ y
2
= p
x
(23)
Integrating these with respect to y for equation (22) and x for equation (23) gives us
_
g
x
dy =
_
y
x
2
+ y
2
dy
. .
I
5
=
_
p
y
dy = p(x, y) + c
3
(24)
_
g
y
dx =
_
x
x
2
+ y
2
dx
. .
I
6
=
_
p
x
dx = p(x, y) + c
4
(25)
The integrals of I
5
and I
6
are just
I
5
=
1
2
ln(x
2
+ y
2
) + (x) (26)
I
6
=
1
2
ln(x
2
+ y
2
) + (y) (27)
For some functions of x and of y. Then using equations (26) and (27) we just have equations (24) and
(25) to be
p(x, y) =
1
2
ln(x
2
+ y
2
) + (x)
p(x, y) =
1
2
ln(x
2
+ y
2
) + (y)
The constants c
3
, c
4
are absorbed into the functions and and we must have (x) = (y) = 0. Hence
p(x, y) =
1
2
ln(x
2
+ y
2
) and we have our analytic function B(x, y) to be
B(x, y) = arctan(
y
x
) +
i
2
ln(x
2
+ y
2
)
5
4 Question 4
The semi-unit disk in the upper half plane is made by all points in the disk e
i
with a line segment on the real
plane which is a real number K such that 1 K 1. The distance of the transformation is given by the
modulus of the transformation of what makes our semi-unit disk: e
i
and K.
Consider |p(e
i
)|. This will determine the distance of the transformation. Taking the square of this removes
the square root (temporarily) and gives us
|p(e
i
)|
2
= p(e
i
)p(e
i
) =
e
2i
+ 2e
i(+

2
)
+ 1
e
i(2+

2
)
+ 2e
i
+ e

i
2
e
2i
+ 2e
i(+

2
)
+ 1
e
i(2+

2
)
+ 2e
i
+ e
i
2
(28)
Expanding equation (28) gives us
1 + 2e
i(

2
)
+ e
2i
+ 2e
i(

2
)
+ 4 + 2e
i(+

2
)
+ 2e
2i
+ e
+

2
+ 1
1 + 2e
i(

2
)
+ e
2i
+ 2e
i(

2
)
+ 4 + 2e
i(+

2
)
+ 2e
2i
+ e
+

2
+ 1
This simplies down to 1. Hence |p(e
i
)|
2
= 1 |p(e
i
)| = 1.
Consider a real number K such that 1 K 1. Then |p(K)| computes the distance of the real number K
in the transformation. Taking the square removes the square root and we have
|p(K)|
2
=
(K
2
2iK + 1) (K
2
+ 2iK + 1)
(K
2
+ 2iK + 1) (K
2
2iK + 1)
=
K
4
+ 2iK
3
+ K
2
2iK
3
+ 4K
2
2iK + k
2
+ 2iK + 1
K
4
+ 2iK
3
+ K
2
2iK
3
+ 4K
2
2iK + k
2
+ 2iK + 1
= 1
= |p(K)|
2
= 1 |p(K)| = 1
We see that both the phase () and line segment (K) are parameterized into the unit circle. So our image
is the unit circle! But how do we know what truly lies inside the transformation? Recall as a consequence of
the Riemann Mapping theorem that any two nite simply connected regions (which our pre-image and image
are) can be mapped (injectively) into each other by a conformal map. p(z) is this injective mapping.
5 Question 5
We convert the function to include logarithms and choose to make it single valued and analytic from there. We
have
q(z) = z
_
1
1
z
=

z 1 = exp(ln((z(z 1))
1
2
) = exp(
1
2
ln(z(z 1))) = exp(
1
2
(ln(z) + ln(z 1)))
The branch points are z = 0 and z = 1. We deduce this by having a small real number near the points 0
and 1 and seeing when makes a full period (so from 0 to 2) a discontinuity appears.
Let z = r
1
e
i
1
and z 1 = r
2
e
i
2
. So we have |r
1
| = z and |r
2
| = |z 1|. Then our function becomes
q(z) = exp
_
1
2
(ln[r
1
r
2
] + ln[e
i(
1
+
2
)
])
_
= e
1
2
ln(r
1
r
2
)
e
i
2
(
1
+
2
)
= (r
1
r
2
)
1
2
e
i
2
(
1
+
2
)
There are several ranges of z and
1
,
2
to consider. We consider z (, 0), z (0, 1), z (1, ).
Branch Cut 1: We have already shifted the origin by representing z in polar form. Let 0
1
,
2
< 2 and
let =

1
+
2
2
. We travel on the positive imaginary axis and also travel on the negative imaginary axis, hence
takes two values! If these two values are the same, we have no problems with continuity and do not need a
branch cut.
For z (, 0) we have = when travelling around the values of . For z (0, ) we have = 0 2
which causes no problems. However for z (0, 1) we have =

2
and =
3
2
. Clearly these are not the same
or equivalent and the discontinuity with the s occurs here.
6
So the only jump occurs on the real axis between 0 and 1, that is, 0 Re z 1. Hence we take our branch
cut here and the function is continuous everywhere but the region (0, 1). The branch cut is (0, 1).
Branch Cut 2: Instead.. suppose we want to make the function continuous only on (0, 1) and cut the
remaining region out, so everything but (0, 1) is removed. Take 0
1
< 2 and
2
< . We have a
branch cut in the region (, 0) (1, ). For z (, 0) we have = and = 0 and for z (0, ) we
have = 0 and = . Clearly none of these are equal or equivalent! However for z (0, 1) we have =

2
and
=

2
. It is continuous here.
The function is now single-valued and continuous for either branch cut. We need to verify that it is analytic.
Recall the Cauchy-Riemann equations in polar form:
u
r
=
1
r
v

,
1
r
u

=
v
r
. We represent our function in
real and imaginary form
q(r, ) = (r
1
r
2
)
1
2
e
i
2
(
1
+
2
)
= (r
1
r
2
)
1
2
_
cos(

1
+
2
2
) + i sin(

1
+
2
2
)
_
Then the real part (u) and imaginary part (v) are
u(r, ) = (r
1
r
2
)
1
2
cos(

1
+
2
2
)
v(r, ) = (r
1
r
2
)
1
2
sin(

1
+
2
2
)
First let r
1
r
2
be represented as some sole number, say r, with r = r
1
r
2
. Similarly let =

1
+
2
2
. The partial
derivatives are
u
r
=
r
1
2
2
cos() (29)
u

=
r
1
2
2
sin() (30)
v
r
=
r
1
2
2
sin() (31)
v

=
r
1
2
2
cos() (32)
We see that equations (29) and (32) satisfy the Cauchy-Riemann equations and so do equations (30) and
(31). Since all partial derivatives are continuous (and the function itself is continuous by taking the branch
cut), for all r and in the specied ranges, the function q(z) is analytic by Theorem 2.
5.1 BONUS: Why is not a branch point?
As z approaches innity, so z , this is a branch point of both associated functions

z and

z 1, should
it also be a branch point of q(z)? It is actually not!
7